2020
DOI: 10.1001/jamanetworkopen.2020.15713
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Including Benchmark Prevalence Data of Common Imaging Findings in Spine Image Reports on Health Care Utilization Among Adults Undergoing Spine Imaging

Abstract: Key Points Question What is the impact of including benchmark prevalence data of common findings in reports of spinal imaging ordered by primary care clinicians? Findings In this randomized clinical trial that included 250 401 adults, no overall decrease in subsequent spine-related health care utilization after the intervention was observed. However, there was a significant decrease in opioid prescriptions at 1 year in the intervention group compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…In addition, consistent with prior research, we found that patients identified as Black/African American, 12,34 identified as Hispanic, 12,34 of higher SES, 14 with no comorbidities, 35 or who received low back imaging in more recent years 7,8 had reduced odds of receiving immediate prescriptions for opioids. Likely, the reduction in opioid prescriptions in the later years of our study was influenced both by the increasing proportion of patients whose images contained the benchmark text for the LIRE study, which was associated with small but significant decreases in the likelihood of subsequent opioid prescriptions, 23 as well as by increasingly broad societal concern about the harms associated with opioid prescriptions. These concerns were summarized in the 2016 Centers for Disease Control and Prevention (CDC) opioid prescribing guidelines, 9 which called attention to the lack of evidence supporting the efficacy of long-term opioid therapy and its potential harms.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, consistent with prior research, we found that patients identified as Black/African American, 12,34 identified as Hispanic, 12,34 of higher SES, 14 with no comorbidities, 35 or who received low back imaging in more recent years 7,8 had reduced odds of receiving immediate prescriptions for opioids. Likely, the reduction in opioid prescriptions in the later years of our study was influenced both by the increasing proportion of patients whose images contained the benchmark text for the LIRE study, which was associated with small but significant decreases in the likelihood of subsequent opioid prescriptions, 23 as well as by increasingly broad societal concern about the harms associated with opioid prescriptions. These concerns were summarized in the 2016 Centers for Disease Control and Prevention (CDC) opioid prescribing guidelines, 9 which called attention to the lack of evidence supporting the efficacy of long-term opioid therapy and its potential harms.…”
Section: Discussionmentioning
confidence: 78%
“…However, patients whose images contained the intervention text had a small but statistically significant decrease in the likelihood of receiving prescriptions for opioids within a year of their index images. 23 For this secondary analysis, all participating institutional review boards determined that the study was minimal risk and granted waivers of consent and Health Insurance Portability and Accountability Act (HIPAA) authorization.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, professional opportunities to manage pain are not always the focus of some disciplines and some disciplines may play a larger role in the care pathway than others and thus arguably may need higher levels of knowledge and attitudes relative to other disciplines. However, each discipline involved in this study may encounter people with pain directly and as such it is important that they all have appropriate knowledge and attitudes to provide patients with clear and consistent high quality basic pain management advice For example, in diagnostic radiography patient interaction may be limited, nevertheless, even if interactions are brief, correct communication is critical [67,68]. Kyei et al (2014) [69] observe the need for good radiographer communication skills because there is only a short time frame available to establish a relationship with patients.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the effectiveness of an intervention developed to address both physician- and patient-related barriers to reducing the use of imaging has not previously been tested. Previous studies have demonstrated reduced imaging examinations with the inclusion of epidemiologic data in lumbar spine MRI reports [ 25 27 ]. In our study, information on the usefulness of imaging was provided to all the patients and professionals, regardless of whether or not imaging was undertaken.…”
Section: Discussionmentioning
confidence: 99%